Przekład kanoniczny i przekład zapomniany – o dwóch młodopolskich tłumaczeniach „Wędrówek Childe Harolda" George’a Gordona Byrona - Nowak, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
This article aims to compare two translations of George Gordon Byron’s poem Childe Harold’s Pilgrimage, which were published only a year apart during the Young Poland period: Jan Kasprowicz’s Wędrówki Rycerza Harolda (1895) and Aleksander Krajewski’s Wędrówki Childe Harolda (1896). A comparative analysis using the methodological background of translation studies shows the equal value of the two translations, one of which is still the basic version of Byron’s work in Polish while the other has been almost entirely forgotten.